EVALUASI PELAKSANAAN PROGRAM RUJUK BALIK TERHADAP KEPATUHAN PASIEN BPJS KESEHATAN DI KLINIK FELLA KABUPATEN SIDENRENG RAPPANG - wakiyah saharani, Nurul Wakiyah Saharani; Pratiwi Ramlan; Khaeriyah Adri; Mardhatillah (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
Patient adherence to the BPJS Health referral program at the Fella Clinic remains suboptimal, indicated by the limited engagement in follow-up appointments and medication adherence for the referral program, which saw a decrease in prevalence by 32.43% from January to October 2023. This research aims to assess patient compliance levels and identify factors contributing to non-compliance with the referral program at the Fella Clinic. Employing a quantitative approach with a cross-sectional design, the study encompassed a population of 148 patients, with a sample size of 60 patients selected through Probability Sampling, specifically Simple Random Sampling. Data collection involved interviews and questionnaires, while analysis utilized the Chi-square test. Out of the 60 respondents, only 5 (8.3%) were non-compliant, whereas 55 (91.7%) were compliant. The Chi-square test results revealed a significant association (p<0.05) between attitudes (p=0.003), knowledge (p=0.005), and family support (p=0.001) with patient compliance regarding the implementation of the BPJS Health referral program at the Fella Clinic.